Contribution of Physical Education in Achieving the Sustainable Develop-ment Goals Agenda 2030: A Scoping Review - Aniciete, Rosa Mae M.; Asuncion, Justine J.; Bulacsao, Ryza M.; Ingal, Raeven Heart G.; Bodilla , Wallie B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
Agenda 2030 serves as a global call to action, aiming to transform lives worldwide. This study summarized literature about PE and Agenda 2030 with the use of a scoping review. The Scopus database was used as the only source of data to identify relevant papers. There was a total of 169 articles extracted, narrowed to 6 relevant studies with the use of PRISMA and PICOS framework. Based on the review, significant findings were revealed that will contribute in the field. The results showed that four various dimensions of PE contribute to SDG 3, (i.e., Creation of Varied Physical Activities Meeting the Learning Standards, Establishment of Holistic Physical and Health Education Programs, Engagement of PE Experts and Stakeholders in Attaining SDG 3 and 4, Empowerment of Stakeholders to Long-Term Benefits of Health and Fitness Engagement). On the other hand, four barriers to PE in terms of pedagogical action toward attaining SDG 4 were identified, (i.e., No Clear Policy Attainment of SDG 4, The Direction of SDG 4 Lacks Teachers' Understanding of the SDG). Lastly, there were three ways PE contributes to attaining SDG 4, (i.e., Adaptation of the Curriculum to Environmental and Societal Changes, Establish Long-Term Goal towards Agenda 2030, Adaptation and Continuous Learning for PE Teachers, Promote Educational Values). The findings of this paper will significantly help stakeholders in the field of PE to strengthen the relationship between PE and SDGs. The general recommendation of this paper is that future work should cover all 17 SDGs to gain more ideas and concepts on how PE can contribute to achieving Agenda 2030.